Perencanaan Sumber Daya Manusia dan Peningkatan Daya Saing Produk melalui Strategi Pengemasan pada Usaha Mikro Seblak Mamih di Kabupaten Bandung - Terra Saptina Maulani; Rr. Rachmawati (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
The creative economy sector is one of the pillars of economic growth in Indonesia where creativity is the basis of economic development activities. West Java Province is one of the provinces in Indonesia with a high distribution of the creative economy sector. Not only is Bandung City famous for its culinary, but currently Bandung Regency is an area that is starting to develop its culinary tourism. in the minds of tourists. One of the snacks or snacks that are popular with the community and also is seblak, this "Seblak Mamih" business has been established for several years, and to develop its business to be competitive where its products can not only be enjoyed by consumers on the spot, an effective and innovative product packaging strategy is carried out so that it can be marketed and enjoyed by consumers more widely. The large number of consumers who come, results in the inability of business owners to serve consumers effectively and efficiently, therefore the need for human resource planning as a party that can serve consumers well.